VDUs and the computer posture. - Persad R (Positive Health)
In the last century of the second millennium A.D. the requirements on the human body are changing. The long days of manual labour and muscular toil have all but gone, and as we spend an increasing number of hours sitting at desks this is having a profound effect upon our physical well being. In the late twentieth century the workplace has changed to incorporate computer terminals at every level, from the executive with his lap top to the mechanic checking the availability of car parts.